Estradiol-sensitive projection neurons in the female rat preoptic area - Sakuma, Yasuo (Frontiers in Neuroscience, 2015)
Electrical stimulation of the preoptic area (POA) interrupts the lordosis reflex, a combined contraction of back muscles, in response to male mounts and the major receptive component of sexual behavior in female rat in estrus, without interfering with the proceptive component of this behavior or solicitation. Axon-sparing POA lesions with an excitotoxin, on the other hand, enhance lordosis and diminish proceptivity. The POA effect on the reflex is mediated by its estrogen-sensitive projection to the ventral tegmental area (VTA) as shown by the behavioral effect of VTA stimulation as well as by the demonstration of an increased threshold for antidromic activation of POA neurons from the VTA in ovariectomized females treated with estradiol benzoate (EB). EB administration increases the antidromic activation threshold in ovariectomized females and neonatally castrated males, but not in neonatally androgenized females; the EB effect is limited to those that show lordosis in the presence of EB. EB causes behavioral disinhibition of lordosis through an inhibition of POA neurons with axons to the VTA, which eventually innervate medullospinal neurons innervating spinal motoneurons of the back muscle. The EB-induced change in the threshold or the axonal excitability may be a result of EB-dependent induction of BK channels. Recordings from freely moving female rats engaging in sexual interactions revealed separate subpopulations of POA neurons for the receptive and proceptive behaviors. Those POA neurons engaging in the control of proceptivity are EB-sensitive and project to the midbrain locomotor region (MLR). EB thus enhances lordosis by reducing excitatory neural impulses from the POA to the VTA. An augmentation of the POA effect to the MLR may culminate in an increased locomotion that embodies behavioral estrus in the female rat.